2019
DOI: 10.1021/acsnano.8b09681
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Assembly of Cell-Mimicking Nanoparticles via a Molecular Affinity Strategy for Targeted Drug Delivery

Abstract: Cell membrane cloaking is an emerging field in drug delivery in which specific functions of parent cells are conferred to newly formed biomimetic vehicles. A growing variety of delivery systems with diverse surface properties have been utilized for this strategy, but it is unclear whether the affinity of membrane−core pairs could guarantee effective and proper camouflaging. In this study, we propose a concise and effective "molecular affinity" strategy using the intracellular domain of transmembrane receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 43 publications
0
54
0
1
Order By: Relevance
“…Meanwhile, the antibacterial effect was no better than vancomycin, which has faced serious problem of drug resistance. In summary, abundant studies have proved that RBCM-based nanoparticle systems are playing a promising role in delivering antibiotics [37]. However, there is still a lot of improvements to make, such as exploring dosage form of novel antibiotics, relatively simple preparation, safety and efficacy studies both in vitro and in vivo and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the antibacterial effect was no better than vancomycin, which has faced serious problem of drug resistance. In summary, abundant studies have proved that RBCM-based nanoparticle systems are playing a promising role in delivering antibiotics [37]. However, there is still a lot of improvements to make, such as exploring dosage form of novel antibiotics, relatively simple preparation, safety and efficacy studies both in vitro and in vivo and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This inspires coating RBC membranes or other cell membranes to nanoparticles, camouflaging them in vivo and making them escape from the monitoring of the immune system. Studies have shown that RBC membranes with abundant self-markers can help the nanoparticles to escape from the recognition of the immune system, greatly extending the circulation half-life of poly(lactic-co-glycolic acid) (PLGA) nanoparticles from a few hours to approximately 40 h [7,8,9,10]. Our studies also demonstrated that RBC membrane-coated melanin, polypyrrole nanoparticles, or gold nanorods exhibited a longer blood circulation time and a higher tumor accumulation compared with bare melanin, polypyrrole nanoparticles, or gold nanorods [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A “molecular affinity” strategy was used to ensure the right‐side‐out orientation of RBC membrane on nanomaterials. [ 159 ] Cytoplasmic protein P4.2 would specifically recognize the intracellular domain of band 3, a transmembrane receptor of RBCs. Therefore, RBC membranes could coat on P4.2‐derived peptide‐anchored liposome with right‐out‐side orientation.…”
Section: Discussionmentioning
confidence: 99%